Merancang Komunikasi Terestrial Inframerah Optik Ruang Bebas Untuk Konektivitas Perkotaan : MRT Indonesia - Monica Putri, Aulya; Fadilla, Enrico Naufal; Sugesti, Erna Sri (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This research titled "Designing Terrestrial Infrared Free Space Optics Communication for Urban Connectivity: MRT Indonesia" explores the application of Free Space Optics (FSO) technology in the Mass Rapid Transit (MRT) transportation system in Indonesia. Utilizing 16-QAM modulation and MIMO antennas, this study demonstrates that FSO can provide efficient and reliable communication, even in challenging weather conditions. Solutions for curved routes or those without Line of Sight (LoS) are also identified, including the use of FSO, optimal route selection, and the installation of repeaters or relay stations. The benefits resulting from the implementation of this technology include fast and reliable connectivity, flexibility in route adjustment, and enhanced security and privacy for passengers.